Les facteurs de satisfaction et d’insatisfaction aux cycles supérieurs dans les universités québécoises francophones - Gemme, Brigitte; Gingras, Yves (Canadian Journal of Higher Education, 2006)
Elucidating the factors that determine the level of satisfaction of graduate students may help us explain the high attrition rates observed in master’s and doctoral programs. Based on a survey of nearly one thousand students and graduates of master’s degree and PhD programs in Québec’s francophone universities, this paper examines the variables affecting their overall satisfaction from their studies. The fi ndings suggest that the factors most closely related to research training are strongly associated with satisfaction. These factors include supervision and the capacity to produce and publish research results. Moreover, the type of funding secured by students is signifi cantly associated with global satisfaction, while gender and age are not. The study concludes that supervised socialization into the role of professional researcher contributes to students’ success in graduate programs.